ANALISIS STRATEGI GURU DALAM MENGATASI DISIPLIN BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS II SDK DON BOSCO 4 KUPANG - Lodiana Benu; Kristina E. Noya Nahak; Chintia M.P Ati (STKIP Subang, 2026)
This study aims to describe teacher strategies in addressing students’ learning discipline problems in the subject of Pancasila and Civic Education (PPKn) in Grade II at SDK Don Bosco 4 Kupang, as well as to identify the impact of implementing these strategies on students’ learning behavior. Learning discipline is an important factor in supporting the success of the learning process, particularly for lower-grade elementary school students who still require intensive guidance. This research employed a qualitative approach using a descriptive method. Data were collected through observations of the learning process, interviews with one Grade II teacher and two students, and documentation in the form of school regulations and learning materials. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that teachers implemented various strategies, including providing role models, establishing and enforcing classroom rules, giving positive reinforcement, and habituating orderly behavior. The implementation of these strategies had a positive impact on improving students’ learning discipline, although some students were still inconsistent in applying them.